Thermal response of a PVCL–HA conjugate. Issue 3 (11th August 2015) - Niskanen, Jukka; Karesoja, Mikko; Aseyev, Vladimir; Qiu, Xing‐Ping; Winnik, Françoise M.; Tenhu, Heikki
ABSTRACT: The synthesis and self‐assembling of a thermoresponsive conjugate of hyaluronic acid (HA) and poly( N ‐vinylcaprolactam) (PVCL) is reported. Both polymers were end functionalized: HA via reductive amination, thereby introducing an azide endgroup to the chain end, and PVCL via thioetherification to introduce a propargyl group. The two were coupled with a copper assisted "click" reaction into a bioconjugate composed of HA blocks with the molar mass 3, 600 g mol −1 (1618 saccharide units) and PVCL blocks of 3, 500 g mol −1 (∼25 repeating units). The cloud point temperature measured by transmittance was 50–51 °C in water. The calorimetrically observed phase transition temperature of PVCL in the conjugate increased by 2 °C to 47.7 °C, whereas the enthalpy of the phase transition was unaffected by the conjugation. HA‐PVCL conjugate self‐assembles in water upon heating into monodisperse, colloidally stable, hollow spherical particles whose size may be tuned with the heating rate of the solution. Slow and fast heating resulted in vesicles with the hydrodynamic radii of 443 or 275 nm, respectively. The heating rate did not, however, affect the cloud point. Salt did not noticeably affect the size of the polymer particles, presumably because of interactions between the HA and PVCL blocks. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 425–436 Abstract : Diblock copolymers consisting of hyaluronic acid, HA, and poly( N ‐vinylcaprolactam), PVCL, have been synthesized. The blocks were first end functionalized and then coupled with click chemistry. The HA block consisted of 16–18 saccharide units and the PVCL block of ∼25 repeating units. HA‐PVCL conjugate self‐assembles in water upon heating into monodisperse, colloidally stable, hollow spherical particles whose size may be tuned with the heating rate of the solution.